Design and fabrication of submicron period grating as an imprinted light guide plate for a backlight unit. Issue 4 (2nd October 2019) - Choi, Hwan-young
ABSTRACT: The imprinted light guide plate (LGP) fabricated through a diffractive grating was studied for the edge-lit display. Such kind of backlight unit (BLU) can save prismatic sheets. The grating dimension was determined through preliminary experiments, modeling, and computation. Based on the designed parameters, a submicron period grating was fabricated and was transferred to the LGP. Consequently, the outcoupling luminous flux, on-axis luminance, and homogeneousness and chromatic dispersion were measured through the prototyped samples. Compared to the conventional BLU, the imprinted diffractive grating works well as the light extractor but still needs to be improved to meet the illumination characteristics required for the liquid crystal display (LCD) BLU.